Modulating lights aerodrome simulators in aviation training visual environment - Квач, Ю.М. (Proceedings of National Aviation University, 2007)
There was considered the possibility of the air field lights simulation in the imitators of flight simulator. The attempt of forming the database of the air field lights with realization in the lighting program DIALux is presented in this paper.